Vector Atomic Magnetometer with Free Induction Decay Detection Based on a Microfabricated Vapor Cell - Pengbo Jiang; Qi Li; Jianan Qin; Zhiyuan Jiang (Micromachines)
Atomic magnetometers are highly sensitive instruments widely used for measurements of weak magnetic field. Extracting vector information while maintaining high-precision scalar detection has become the trend in atomic magnetometer development. We introduce a vector atomic magnetometer containing a 5 mm-thick microfabricated vapor cell operating in free-induction-decay mode. By employing orthogonal modulation techniques, the system achieves high-precision in-plane vector magnetic field measurements. The high-precision vector magnetic field measurements are demonstrated in the x–z plane. The sensitivity of the total field detection in the miniaturized atomic magnetometer is 30 pT·Hz−1/2 @11 µT. The average angular error of the decoupled measurement is as low as 4.7 mrad @7.6 µT for vector magnetic fields, providing a new approach for vector magnetic field measurement in miniaturized atomic magnetometers.